«Բանք իմաստասիրաց» ժողովածուի հունարեն աղբյուրը - Մուրադյան, Գոհար
The Sayings of the Philosophers (called sometimes Sayings of Sages) are extant in numerous Armenian manuscripts. Their contents, like those of the Greek gno- mologia, strongly vary. Ruzanna Poghosyan’s article in the present volume contains a critical edition of one of the recensions of that text, which she compiled on the basis of three 14th c. manuscripts. It consists of 200 sayings, divided into 23 thematic groups: the first section (1-10) has no subtitle, but could be entitled “Concerning prudence”; the rest are entitled as follows: “Concerning courage,” “Concerning friends,” “Concerning rulers,” “Concerning swearing,” “Concerning education,” “Concerning fate,” “Concerning conscience,” “Concerning physicians,” “Concerning evil women,” “Concerning law,” “Concerning care”, “Concerning wealth,” “Concerning drunkenness,” “Concerning the honor of parents,” “Concerning flattery,” “Concerning noble birth,” “Concerning silence,” “Concerning judgement,” “Concerning glory,” “Concerning death,” “Concerning rulers” (the same as the 4th section), “Concerning deity.” Our search for their possible Greek sources led to the conclusion that the collection in question is a translation of a Greek original which belongs to the “family” of the collection called Loci communes ascribed to Maximus the Confessor (probably compiled in the 9th or early 10th c.), not to its long recension divided into 71 sections, but to an abridged recension. At least 175 sayings of the 200 in the Armenian version have parallels in that collection, the majority of them being exact translations from the Greek. 148 of the 175 are also present in the Corpus Parisinum which is regarded the main source of the Loci communes, 63 are also found in Stobaeus’ Anthology, which in its turn is the source of the Corpus Parisinum. One saying finds a parallel in the collection of Secundus the Silent philosopher, and another in the Lives of Philosophers of Diogenes Laertius. In the case of the remaining three entries we have failed to find Greek parallels. «Изречения философов» (иногда такие сборники называются «Изречения мудрецов») сохранились во множестве армянских рукописей. Их состав и содержание, как и в греческих гномологиях, сильно варьируется. В статье Рузанны Погосян в данном номере журнала помещен составленный ею критический текст одного из вариантов сборника изречений на основе трех рукописей XIV века. Он состоит из двухсот изречений, разделенных на 23 тематических раздела: подзаголовок первого раздела (1-10) отсутствует, но его можно было бы назвать «О рассудительности»; остальные озаглавлены: «О мужестве», «О друзьях», «О правителях», «О клятве», «Об образовании», «О судьбе», «О признании», «О врачах», «О злых женах», «О законе», «О пoпечении», «О богатстве», «О пьянстве», «О почитании отцов», «О лести», «О благородстве», «О молчании», «О суждении», «О славе», «О смерти», «О правителях» (та же тема, что и 4-ая группа), «О божестве». Поиски их возможных греческих источников привели нас к тому, что собрание является переводом греческого сборника, относящегося к «семейству» Loci communes, приписываемого Максиму Исповеднику (предположительно IX век или начало X), но не полной его версии, состоящей из 71-го раздела, а какого-то сокращенного варианта. По крайней мере 175 из двухсот армянских высказываний имеют параллели с изречениями в этом сборнике, а многие являются их дословным переводом. 148 из этих 175-и присутствуют также в Corpus Parisinum (вероятно, VIII век), который считается главным источником собрания Loci communes, а 63 – в антологии Стобея, источнике «Парижского корпуса». Два изречения имеют параллели соответственно в сборниках Секунда Молчаливого и в «Жизни, учениях и изречениях знаменитых философов» Диогена Лаэртского. Для оставшихся трех апофтегм найти греческие параллели не удалось.
Keywords: Հրապարակումներ; Ձեռագրական մշակույթ